2008
DOI: 10.1124/dmd.108.021402
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative in Vitro Metabolism of Liquiritigenin, a Bioactive Compound Isolated from the Chinese Herbal Selective Estrogen β-Receptor Agonist MF101

Abstract: ABSTRACT:Liquiritigenin [2,3-dihydro-7-hydroxy-2-(4-hydroxyphenyl)-(S)-4H-1-benzopyran-4-one] is one of the major active compounds of MF101, an herbal extract currently in clinical trials for the treatment of hot flashes and night sweats in postmenopausal women. MF101 is a selective estrogen receptor ␤ agonist but does not activate the estrogen receptor ␣. Incubation with pooled human liver microsomes yielded a single metabolite. Its structure was elucidated using tandem mass spectrometry in combination with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…The metabolite (M1) was observed as negative molecule [M-H] − at m/z 253 ( = 255 − 2, consistent with a loss of two hydrogens). The fragmentation patterns and exact masses of the parent and fragments were confirmed with 7,4-dihydroxyflavone ( Figure 3C), which was in accord with the CYP3A4-catalyzed metabolite described by Kupfer et al (2008). The metabolite (M2) was observed as negative molecule [M-H] − at m/z 271 ( = 255 + 16, consistent with a direct hydroxylation).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The metabolite (M1) was observed as negative molecule [M-H] − at m/z 253 ( = 255 − 2, consistent with a loss of two hydrogens). The fragmentation patterns and exact masses of the parent and fragments were confirmed with 7,4-dihydroxyflavone ( Figure 3C), which was in accord with the CYP3A4-catalyzed metabolite described by Kupfer et al (2008). The metabolite (M2) was observed as negative molecule [M-H] − at m/z 271 ( = 255 + 16, consistent with a direct hydroxylation).…”
Section: Discussionsupporting
confidence: 66%
“…In recently published study of the oxidative metabolism of liquiritigenin by using HLMs, Kupfer et al (2008) found only one metabolite (7,4′-dihydroxyflavone). In vitro metabolism of liquiritigenin with RLMs, however, yielded six metabolites (7,3′,4′-trihydroxyflavone, a hydroxyl quinine metabolite, two A-ring dihydroxymetabolites, 7,4′-dihydroxyflavone, and 7-hydroxychromone) (Nikolic & van Breemen, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we have found that liquiritigenin does not induce the proliferation of MCF-7 or T47D breast cancer cells (unpublished observations), which is consistent with the results of other studies (Gustafsson et al, 2003). Finally, pharmacokinetics data has demonstrated that liquiritigenin is absorbed well by the intestine amongst rats, with an in vitro blood-brain barrier penetration rate of (29.7±6.8)% within 90 min, similar to that of chloramphenicol (34.0±4.9)%, a known blood-brain barrier and highly penetrative drug (Kupfer et al, 2008;Lu et al, 2008;Kang et al, 2009). Taken together, these observations suggest that liquiritigenin may be a potentially effective therapy for AD.…”
Section: Introductionsupporting
confidence: 79%
“…Liquiritigenin (7, 4'-dihydroxyflavanone) is a flavonoid extracted from the radix of Glycyrrhiza, an herbal that is frequently used to treat injury or swelling, or for detoxification in traditional Oriental medicine. Liquiritigenin is also one of the major active compounds of MF101 (Kupfer et al, 2008), an herbal extract currently used in clinical trials for the treatment of hot flushes and night-sweats in post-menopausal women. Our interest in liquiritigenin is based upon the following observations.…”
Section: Introductionmentioning
confidence: 99%